A COPARATIVE STUDY OF CASTRATION IN PIGS - N.Al-Asadi, , R.; I. Salih, S. (The Iraqi Journal of Veterinary Medicine, 1992)
Castration was performed on 46 pigs aged between (2-8) months using open and closed methods under the effect of local and general anaesthesia .Secondary complication includes bleeding, odema and peritonitis occured in seven cases when using open method while the remaining animals healed by first intenstion. only. In closed method, secondary complication was observed in one animal The results of the present study indicated the preference of using closed method castration in pigs.